AB0964 Dactylitis Ultrasonographic Features Correlation to Dermatological, Genetic and Activity Indices in Early Psoriatic Arthritis Patients. (10th June 2014) - Bandinelli, F.; Prignano, F.; Denaro, V.; Collaku, L.; Melchiorre, D.; Sladojevic, S.; Matucci Cerinic, M.
Abstract : Background: In early phase of Psoriatic arthritis (ePsA), US abnormalities might be sub-clinical and independent to psoriasis. Objectives: To investigate the ultrasonography (US) dactylitis abnormalities in early PsA patients and to compare them to dermatological, genetic and activity indices. Methods: 112 early PsA diagnosed with CASPAR criteria, were studied with MyLab70 Xview (linear probe 15 MHz) US examination of hand fingers. At US, were evaluated the Power Doppler positive synovitis (PS), the tenosynovitis-peritendinitis (TP) of flexors/extensors and the pseudotenosynovitis (PT) (PD subcutaneous signal around flexor tendons) and their correlation with dermatological (presence/absence of psoriasis, presence/absence of palmar psoriasis, presence/absence of nail dystrophy, PASI), genetic (positivity/negativity of HLAB27, B35, B38, CW6, CW7, DR1, DR4) and activity indices (BASDAI, HAQ modified for spondyloarthritis [SHAQ], normality or elevation of ESR, CRP). Results: At US, in ePsA, US abnormalities at fingers were present in different percentage: 25, 9% (29/112) PD positive synovitis (PS), 17, 8% (20/112) tenosynovitis-peritendinitis (TP), 14, 3% (16/112) pseudotenosynovitis (PT). At Yates X square test analysis, US parameters correlated to the presence of these three parameters: psoriasis (all p<0, 0001), palmar psoriasis (PS p<0, 005), nail dystrophy (PS p<0, 05, PT p<0, 0001), B27 (PS p<0, 0001, TP p<0, 01, PT p<0, 05), B35 (PS p<0, 05), B38 (PS p<0, 0001, TP p<0, 0001, PT p<0, 005), CW7 (PS p<0, 0001), DR4 (PS p<0, 0001, TP p<0, 0001, PT p<0, 005), CRP (all p<0, 0001), ESR (PS p<0, 0005, TP p<0, 0001, PT p<0, 0001). At Pearson correlation, US abnormalities are independent to PASI, BASDAI and SHAQ. Conclusions: Dactylitis US abnormalities are correlated to the presence of psoriasis, HLA aplotypes B27-B35-B38-CW7-DR4 and CRP/ESR elevation, while are independent to severity of dermatologic involvement and clinical indices. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4283